2020
DOI: 10.3390/fractalfract4030037
|View full text |Cite
|
Sign up to set email alerts
|

Design of Cascaded and Shifted Fractional-Order Lead Compensators for Plants with Monotonically Increasing Lags

Abstract: This paper concerns cascaded, shifted, fractional-order, lead compensators made by the serial connection of two stages introducing their respective phase leads in shifted adjacent frequency ranges. Adding up leads in these intervals gives a flat phase in a wide frequency range. Moreover, the simple elements of the cascade can be easily realized by rational transfer functions. On this basis, a method is proposed in order to design a robust controller for a class of benchmark plants that are difficult to compens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…They are: the fractional order  (or equivalently the approximate phase angle i), the value Fo in (1), the frequency limits of the constant-phase bandwidth (CPB) L and H (or equivalently the specified bandwidth BW=H/L and the central frequency c), the phase deviation  (or Gmax/Gmin) representing the specified maximum allowable phase variation within the CPB limits as shown in Fig. 2, and the function order N (or approximation order n) 7 . The approximation methods used for the comparison are presented in chronological order.…”
Section: A Comparison Of the Minimax Approximation To Other Approximation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are: the fractional order  (or equivalently the approximate phase angle i), the value Fo in (1), the frequency limits of the constant-phase bandwidth (CPB) L and H (or equivalently the specified bandwidth BW=H/L and the central frequency c), the phase deviation  (or Gmax/Gmin) representing the specified maximum allowable phase variation within the CPB limits as shown in Fig. 2, and the function order N (or approximation order n) 7 . The approximation methods used for the comparison are presented in chronological order.…”
Section: A Comparison Of the Minimax Approximation To Other Approximation Methodsmentioning
confidence: 99%
“…This awareness has resulted in the increased development of fractional calculus applications in various fields of engineering and science. They include more efficient PI  D  controllers compared to conventional PID controllers [3]- [6], more precise lead/lag compensators [7] [8], a FO model that efficiently approximates the electroencephalographic measurement chain system [9], high-speed FO PLLs with broader capture range and bandwidth, lower phase error and shorter locking time [10], active-RC FO filters that allow for a fractional step in the stopband [11]- [15], FO resonators which can have infinite Q-factors [16], FO oscillators for very high or very low frequency signals [17], FO band-pass filters and resonators realized in integrated form allowing low frequency operation, huge inductance values and electronic tunability of order and other parameters [18] [19]. Besides, Westerlund has shown that capacitors with dielectric can only be modelled accurately with FO derivatives [20], because nature works with FO derivatives [21].…”
Section: Introductionmentioning
confidence: 99%
“…Example IV.1. The fractional lead (+α) compensator used in Control to increase the phase of a system around a chosen frequency and the lag (−α) compensator, used to increase the static gain of a plant, are defined by the TF [114], [23], [115] C(s) = τ s + a s + a (…”
Section: B On the Tempered Lsmentioning
confidence: 99%